Here's the question you clicked on:
Spartan_Of_Ares
can some one help me with 7 rational expressions?
\[\frac{ x+2 }{ (x-4)^{2} }- \frac{ x }{x-4 }\] this is my first one
hey @Hero can you help me out?
Hint: Multiply the second fraction by (x-4)/(x-4)
\[\frac{ x^2-4 }{ x^2-16 }?\]
@Hero is this right?
how would i go about doing this?
I'm only going to show you this once.
\[\space\space\space\space\frac{x + 2}{(x - 4)^2} - \frac{x}{x-4}\]\[=\frac{x + 2}{(x - 4)^2} - \frac{x}{x-4} \times\frac{x-4}{x-4}\]\[=\frac{x + 2}{(x - 4)^2} - \frac{x(x-4)}{x-4(x-4)}\]\[=\frac{x + 2}{(x - 4)^2} - \frac{x^2-4x}{(x-4)^2}\]\[=\frac{(x + 2) - (x^2 - 4x)}{(x-4)^2}\]\[=\frac{x + 2 - x^2 + 4x}{(x-4)^2}\]\[=\frac{-x^2 + 4x + x + 2}{(x-4)^2}\]\[=\frac{-x^2 + 5x + 2}{(x-4)^2}\]\[=\frac{-(x^2 - 5x - 2)}{(x-4)^2}\]\[=-\frac{x^2 - 5x - 2}{(x-4)^2}\]
thanks allot for the help!